2019
DOI: 10.1038/s41579-019-0149-x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus entry and how to block it

Abstract: AlveoliSmall air sacs in the lung that provide rapid gas exchange with blood. BronchiolitisInflammation of the bronchioles that reduces air passage. FormalinAn aqueous solution of formaldehyde.Abstract | Respiratory syncytial virus (RSV) is a leading cause of lower respiratory tract disease in young children and elderly people. Although the virus was isolated in 1955, an effective RSV vaccine has not been developed, and the only licensed intervention is passive immunoprophylaxis of high-risk infants with a hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
211
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(249 citation statements)
references
References 171 publications
3
211
0
5
Order By: Relevance
“…several key respiratory viruses ( Figure S3) (Battles and McLellan, 2019;Bochkov and 240 Gern, 2016; Laporte and Naesens, 2017; Peck et al, 2015). For examples, consistent 241 with prior findings, we found that CDHR3, a receptor for Rhinovirus C, was expressed 242 most abundantly in ciliated cells (Battles and McLellan, 2019;Bochkov and Gern, 2016;243 Laporte and Naesens, 2017; Peck et al, 2015).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…several key respiratory viruses ( Figure S3) (Battles and McLellan, 2019;Bochkov and 240 Gern, 2016; Laporte and Naesens, 2017; Peck et al, 2015). For examples, consistent 241 with prior findings, we found that CDHR3, a receptor for Rhinovirus C, was expressed 242 most abundantly in ciliated cells (Battles and McLellan, 2019;Bochkov and Gern, 2016;243 Laporte and Naesens, 2017; Peck et al, 2015).…”
supporting
confidence: 82%
“…several key respiratory viruses ( Figure S3) (Battles and McLellan, 2019;Bochkov and 240 Gern, 2016; Laporte and Naesens, 2017; Peck et al, 2015). For examples, consistent 241 with prior findings, we found that CDHR3, a receptor for Rhinovirus C, was expressed 242 most abundantly in ciliated cells (Battles and McLellan, 2019;Bochkov and Gern, 2016;243 Laporte and Naesens, 2017; Peck et al, 2015). ANPEP, the entry receptor for HCoV-244 229E, was predominantly expressed in macrophages and to a lesser extent in club and 245 other epithelial cells (Waradon Sungnak, 2020; Yeager et al, 1992).…”
mentioning
confidence: 99%
“…Source file: F, fusion protein; G, glycoprotein; L, large nucleoprotein; M, matrix protein; NS, nonstructural protein; P, phosphoprotein; RSV, respiratory syncytial virus; ssRNA, single-stranded RNA (reproduced with permission). 33 adults are still less likely to have a positive result. 31 While sensitivity is greatly reduced in older patients, they remain the most sensitive detection method available.…”
Section: State Of the Art Review Box 1 Adults Are Less Likely To Testmentioning
confidence: 97%
“…The initial events in RSV sensing are well-understood. After viral binding and fusion [19], RSV genomic RNA and its nucleoprotein complex including RNA-dependent RNA polymerase are released into the cytoplasm, where the polymerase produces capped and polyadenylated mRNAs encoding viral proteins in cytoplasmic inclusion bodies [20], becoming sites of viral RNA synthesis and production of innate immune responses. In epithelial cells, UV cross-linking immunoprecipitation PCR experiments have demonstrated that RSV RNA is primarily sensed by RIG-I [21].…”
Section: The Airway Epithelial Cell As a Sensor Of Rsv Replicationmentioning
confidence: 99%